Paspalum schesslii (Poaceae, Paspaleae), a new species from Mato Grosso (Brazil) with an unusual base chromosome number - Bonasora, Marisa Graciela (2015)
Paspalum schesslii, a new species from the state of Mato Grosso in central-western Brazil, is described and illustrated. The new species is related to P. malmeanum, from central-western Brazil and eastern Bolivia, and Paspalum eucomum, from central Brazil. It comprises shorter plants with leaf blades and racemes shorter than those of the related species, and spikelets having obovate, deciduous upper florets. An unexpected chromosome number 2n = 12 was found in specimens of P. schesslii; thus it differs from both P. malmeanum, which has 2n = 20, and P. eucomum, for which 2n = 30 and 2n = 32 chromosome counts are here reported for the first time. The discovery of a new species having 2n = 12, which often cohabits with diploid populations of the widespread related species, P. stellatum, is consistent with an hypothesis about the hybrid origin of the polyploid cytotypes of P. stellatum having 2n = 32 and 2n = 52 chromosomes. Moreover, such an hybrid origin involving parental species with different base chromosome numbers (x = 6 and x = 10) could also explain the occurrence of 32 chromosomes in P. eucomum, potentially documenting a speciation mechanism that is otherwise unknown in the genus.